Friends for the benefits: The effects of political ties on sovereign borrowing conditions - Gene Ambrocio; Iftekhar Hasan (Bank of Finland, 2019)
Do closer political ties with a global superpower improve sovereign borrowing conditions? We use data on voting at the United Nations General Assembly along with foreign aid flows to construct an index of political ties and find evidence that suggests closer political ties leads to both better sovereign credit ratings and lower yields on sovereign bonds. We use heads-of-state official visits and coalition forces troop contributions as exogenous instruments to further strengthen the findings.
URN:NBN:fi:bof-201907221301
Keywords: F50; F35; H63; G24; 330